Removal mechanism of liquid-assisted nanosecond pulsed laser cleaning TA15 titanium alloy oxide film - Zhichao Li; Xi Chen; Shirui Yang; Donghe Zhang; Jie Xu; Rui Ma; Debin Shan; Bin Guo (Journal of Materials Research and Technology, 2022)
Liquid-assisted pulsed laser cleaning is achieved by coating kerosene on titanium alloy oxide film, and the surface was processed to form micro- and nanostructured amorphous-nanocrystalline phases oxidized layer after laser cleaning. The surface morphology is acquired by changing the laser fluence (F) and spot overlap ratio (Ux = Uy) with ﬁeld emission scanning electron microscopy (FE-SEM) and atomic force microscopy (AFM). The surface composition change was analyzed by X-ray photoelectron spectroscopy (XPS). The transmission electron microscopy (TEM) was used to analyze the sample section. The surface quality is optimal when the laser fluence is between 5.095 J/cm2 and 6.37 J/cm2 at the spot ratio of 70%. The ridge structure appears on surface when the laser fluence exceeds 7.644 J/cm2. The original oxide film consisted of titanium oxides (Ti4+ and Ti3+) and C-containing contaminants. Ti0 peak appears on the surface at 6.37 J/cm2 and TiC might be formed on the surface for new peak (281.6 eV). The martensitic heat-affected layer was formed about 2.33 um at 6.37 J/cm2, and surface oxide layer is only about 12 nm. The removal mechanisms of liquid-assisted laser cleaning titanium alloy oxide film are laser-induced shock wave, laser ablation and phase blasting at difference fluence. Liquid-assisted laser cleaning technology can provide an effective surface cleaning and material processing process.